El espectáculo dramático-festivo del Corpus en la Salamanca del Renacimiento - Framiñán de Miguel, María Jesús; TC/12 (Research project) (Madrid : Iberoamericana ; Frankfurt am Main : Vervuert Verlag, 2015)
This book traces the panorama of scenic, theatrical and musical activity that, according to its sources, took place in the city of Tormes during the 16th and first decade of 17th century on the occasion of the fun and festive Eucharistic celebration.
Origen de la festividad del Corpus Christi -- La procesión : marco religioso del festejo -- Organización y presupuesto del festejo -- Producción propria : auto y danza de la catedral -- El Corpus entre 1500 y 1530 -- El Corpus entre 1531 y 1560 -- El Corpus entre 1561 y 1590 -- El Corpus entre 1590 y 1610 -- El Corpus de la parroquia de San Martín : 1574-1578 -- Un desfile lúdico-festivo : la procesión del Arzobispo -- Sebastián de Granadilla y el Corpus : 1573, 1577, 1580, 1598 -- La práctica escénica : 1501-1610 -- La actividad musical : 1501-1513 -- Gráficas, evolución del gasto -- Relación cronológica de obras y actividades escénicas.
This volume originated from a doctoral thesis "Teatro en Salamanca (1500-1627). Estudio y documentos" defended on January 27, 2012 at Universidad de Salamanca.
Includes bibliographical references.
Online resource; title from PDF title page (Digitalia, viewed April 30, 2019)
Keywords: Corpus Christi Festival -- Spain -- Salamanca -- History -- 16th century; Corpus Christi Festival -- Spain -- Salamanca -- History -- 16th century -- Sources; Theater -- Spain -- Salamanca -- History -- 16th century; Theater -- Spain -- Salamanca -- History -- 16th century -- Sources; Salamanca (Spain) -- Religious life and customs -- 16th century; Electronic books